ENGLISH FOR SPECIFIC PURPOSES DIUNIVERSITAS JEMBER:TANTANGAN DAN SOLUSI - Kusumaningputri, Reni (Jurnal Pengembangan Pendidikan, 2010)
Abstract. ESP (Englishfor Specific Purposes) course faces many problems. This article is aimed atdescribing those and giving some alternative solutions. The problems which layon the teachers, materials, learners, and policy of the institution, hamper thesignificance of the course to the learners, institutions, and alsostakeholders. In order to minimize these effects, some solutions are offered.The solutions are materials development, changes on the policies of curriculum,learners, and the commitment of the institution. Â Key words: English for Specific Purposes, material development, university policy